2021
DOI: 10.1186/s12916-021-01993-8
|View full text |Cite
|
Sign up to set email alerts
|

Community-based molecular and serological surveillance of subclinical malaria in Myanmar

Abstract: Background In the Greater Mekong Subregion (GMS), current malaria surveillance strategies rely on a network of village health volunteers (VHVs) reporting the results of rapid diagnostic tests (RDTs), known to miss many asymptomatic infections. Integration of more sensitive diagnostic molecular and serological measures into the VHV network may improve surveillance of residual malaria transmission in hard-to-reach areas in the region and inform targeted interventions and elimination responses. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 41 publications
2
12
0
Order By: Relevance
“…These infections also show reduced parasite genetic diversity [ 9 ], fewer infective Anopheles [ 10 , 11 ], lower adherence to anti-malarials drug regimens [ 12 14 ], and increased asexual parasite clearance rates [ 9 , 15 ]. Previous studies of submicroscopic parasitaemia have primarily been concerned with its occurrence in pregnant women [ 16 20 ] and cross-sectional community surveys of asymptomatic individuals [ 3 , 21 24 ]. However, fewer studies have focused on its occurrence as it pertains to malaria treatment-seeking behaviour [ 14 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These infections also show reduced parasite genetic diversity [ 9 ], fewer infective Anopheles [ 10 , 11 ], lower adherence to anti-malarials drug regimens [ 12 14 ], and increased asexual parasite clearance rates [ 9 , 15 ]. Previous studies of submicroscopic parasitaemia have primarily been concerned with its occurrence in pregnant women [ 16 20 ] and cross-sectional community surveys of asymptomatic individuals [ 3 , 21 24 ]. However, fewer studies have focused on its occurrence as it pertains to malaria treatment-seeking behaviour [ 14 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Used RDT cassettes and dried blood spots will be kept and stored where possible to extract DNA and antibodies to determine secondary outcomes 2B, 2C, 2D, 2E, 2F, and 2G using PCR and ELISA methods as previously described [ 16 , 19 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…This caveat is particularly problematic in cross‐sectional surveys, where it is impossible to know when the last boosting event occurred, and how the development and kinetics of that response will change the association over time. Further, in regions that have recently transitioned from high/moderate to low transmission where a large proportion of a surveyed population may still be reflected as high responders or as seropositive 71 . The findings of such investigations may provide interesting insight, however, large, observational studies using highly sensitive molecular diagnoses with frequent sampling among returning participants provide the most robust data for assessing associations between acquired immunity and subclinical infection.…”
Section: Humoral Immunity and The Prevalence Of Sub‐clinical Plasmodi...mentioning
confidence: 99%
“…Recent studies have demonstrated an association between Abs and protection from PCR‐detectable subclinical infection. 70 , 71 However, these findings have been reported mostly in serial cross‐sectional surveys, which may fail to capture individual infection dynamics.…”
Section: Maintenance Of Antimalarial Antibodies and Sub‐clinical ...mentioning
confidence: 99%
See 1 more Smart Citation